Operculina turpethum extract inhibits growth and proliferation by inhibiting NF-κB, COX-2 and cyclin D1 and induces apoptosis by up regulating P53 in oral cancer cells. (August 2017) - Arora, Ritu; Bharti, Vijaya; Gaur, Poonam; Aggarwal, Sadhna; Mittal, Manasi; Das, Satya N.
Highlights: Operculina turpathum extract (OTE) induces cytotoxicity in oral cancer cells. It causes cell cycle arrest by downregulating cyclin D1 and induces apoptosis by upregulating p53. It inhibits tumor cell growth by inhibiting NF-κB and COX-2. Abstract: Objectives: Herbal drugs are popularly emerging as complementary and alternative medicines in cancer patients because of their cost effectiveness and minimal side-effects. The extract of Operculina turpethum (OT) is known to have antipyretic, anti-inflammatory and purgative properties. Since it is popularly known have antiinflammatory activity, we investigated its anti-tumor activity on four oral squamous cell carcinoma cell lines (OSCC) namely, (SCC-4, KB, SCC-9 and SCC-25). Design: Antitumor activities of Operculina turpathum extract (OTE) was investigated by MTT and clonogenic assay, effect on cell cycle and apoptosis induction by Annexin-V/propidium iodide (PI) staining and flow cytometry and invasive potential of the tumor was determined by matrigel assay. The expression of various proteins involved in these mechanisms was analysed by western blotting. Results: OTE specifically inhibited the growth and colony formation of OSCC cells in a dose-dependent manner via inhibiting NF-κB and its downstream target COX-2. It further arrested cell cycle at G0/G1 phase by inhibiting cyclin-D1 and induced early apoptosis by up-regulating P53 in OSCC cells. It also limits the invasion capacity of OSCC cells by up to 55–60%. Conclusions: OTE shows antitumor activities in OSCC cells by inhibiting NF-κB, COX-2 and cyclin D1 and upregulation of p53 expression. It may be developed as a safe and promising alternative chemopreventive/chemotherapeutic agent for oral cancer.